Integration of Islamic Values and Nusantara Culture in Buya Hamka’s Educational Thought - Arianto, Dedi; Syafrizal, Syafrizal Fuady; Muhadi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Islamic education in Indonesia has often emphasized solely normative-doctrinal aspects, making it less capable of addressing various contextual challenges and the moral crises faced by the younger generation. This phenomenon indicates a gap between the universal ideals of Islamic teachings and the dynamic socio-cultural realities of society. In this context, Buya Hamka’s thought offers an integrative perspective that seeks to harmonize Islamic values with the local wisdom of the Nusantara, aiming to develop an Islamic education that is more contextual, humanistic, and deeply rooted in the nation’s cultural heritage. This article aims to examine a model of Islamic education based on local values as reflected in the works and ideas of Buya Hamka. The research approach employed is a conceptual paper utilizing hermeneutic analysis and literature synthesis, with a focus on a narrative review of texts and the core concepts found in Buya Hamka’s writings as well as other relevant scholarly literature. This study reveals that Hamka developed an educational model based on three main pillars: aqidah (faith), akhlaq (morality), and knowledge, while remaining open to the integration of local cultural values such as gotong royong (mutual cooperation), musyawarah (deliberation), and customary practices that align with the principles of Sharia. This integration is not a form of compromise but a transformative process that enriches Islamic education with a contextual socio-cultural dimension. Such an approach produces a contextual, character-based, and transformative Islamic education model, making it relevant in addressing the challenges of globalization while reinforcing the nation’s identity. This article provides a conceptual contribution to the development of Islamic education curricula rooted in Islamic values and local wisdom, and it opens avenues for further research on the implementation and policy of value-based education